Effectiveness of Self-Instructional Module (SIM) On Knowledge Regarding Pregnancy Induced Hypertension (PIH) Among Staff Nurses - Sunayana Sangram Holkar; Priyanka Dhumale; Jyoti Aurwade, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background and Objectives: Pregnancy is one of the most significant phases in a woman's life, requiring systematic and continuous care to ensure a safe delivery, early identification of complications, and timely medical intervention. Women, particularly during pregnancy, are considered a vulnerable segment of the population. In India, approximately 23 million births occur annually, with an estimated 24 million pregnancies. Of these, 7–15% are complicated, contributing to a significant burden of maternal health issues. Globally, about 529,000 women lose their lives each year due to pregnancy-related complications, and for every death, nearly 118 women experience life-threatening conditions or severe acute health issues. Pregnancy-induced hypertension (PIH) is a significant contributor to maternal, fetal, and neonatal morbidity and mortality. Women affected by PIH are more susceptible to conditions such as placental abruption, cerebrovascular accidents, organ dysfunction, and disseminated intravascular coagulation. Additionally, fetuses of mothers with PIH are at a heightened risk of experiencing intrauterine growth restriction, preterm birth, and intrauterine death. Pregnancy-induced hypertension (PIH) is a medical condition that develops during pregnancy, characterized by elevated blood pressure. Also referred to as toxemia, PIH typically arises after 20 weeks of gestation in women who previously had normal blood pressure levels. It is clinically defined as a systolic blood pressure exceeding 140 mmHg or a diastolic blood pressure above 90 mmHg. This condition involves increased vascular resistance, often accompanied by vasospasm in both small and large arteries. PIH is observed in approximately 5% to 8% of pregnancies and can impair blood flow to multiple organ systems, including the liver, kidneys, brain, uterus, and placenta. Objectives: 1. To assess the level of knowledge regarding pregnancy induced hypertension (P.I.H) among staff nurses. 2. To evaluate the effectiveness of SIM on knowledge regarding pregnancy induced hypertension (P.I.H) among staff nurses. 3. To find out an association between mean pretest knowledge score regarding pregnancy induced hypertension (P.I.H) with their selected socio- demographic variables. Methods: A quantitative evaluative survey approach was adopted for the present study, utilizing a pre-experimental one-group pre-test and post-test design. After obtaining ethical clearance, prior permission was sought from D.Y. Patil Hospital in Kolhapur. The intervention focused on pregnancy-induced hypertension, aiming to evaluate the effectiveness of a self-instructional module on this topic. According to Slovin's formula, the target population for the study was 124 staff nurses, from which 80 staff nurses were selected as the sample population, considering a margin of error of 0.10. After obtaining consent from the participants, 80 subjects were chosen using a non-probability purposive sampling technique. A pre-test was conducted to assess their knowledge regarding pregnancy-induced hypertension. Subsequently, the self-instructional module was administered to the subjects. A post-test was conducted seven days later, on the eighth day, using the same tool as the pre-test. After data collection, the data were tabulated and analyzed. Based on the interpretation, a scale of Good, Average, and Poor was applied. Results: The findings of this study revealed that the mean post-test knowledge score of the subjects was higher than their mean pre-test knowledge score. The paired t-value was 14.82, with a p-value of 0.01*, which is considered extremely significant. This indicates a notable improvement in knowledge regarding pregnancy-induced hypertension following the intervention. Therefore, the research hypothesis (H₁) was accepted. Interpretation and Conclusion: Descriptive statistics, including the mean and standard error difference for the pre- and post-test, revealed a deficit in knowledge regarding pregnancy-induced hypertension among staff nurses. However, the post-test knowledge scores indicated a significant gain in knowledge following the administration of the self-instructional module. The paired ‘t’ test and 'p' values were computed to assess the effectiveness of the self-instructional module, and the results clearly indicated that the intervention was effective.